The longitudinal relationship of school climate with adolescent social and emotional health - Mitchell D. Wong; Kulwant K. Dosanjh; Nicholas J. Jackson; Dennis Rünger; Rebecca N. Dudovitz (BMC, 2021)
Abstract Background Schools and school climate are thought to influence academic outcomes as well as child and adolescent development, health and well-being. We sought to examine the relationship between several aspects of the school climate with adolescent social-emotional health outcomes. Methods We analysed data from the Reducing Inequities through Social and Educational change Follow-up (RISE UP) Study, a longitudinal natural experimental study of Los Angeles high school students collected from 2013 to 2018. We analysed data on the portion of the sample that completed the baseline, 10th grade and 11th grade surveys (n=1114). Students reported their perceptions of school climate at 10th grade and social-emotional outcomes including grit, self-efficacy, depression, hopelessness, and stress at baseline (9th grade) and at 11th grade. Multivariable regressions adjusted for student and parental demographics and baseline social-emotional states tested associations between school climate and each outcome. Results Students who reported being in authoritative school environments in 10th grade, one that is highly supportive and highly structured, had subsequently higher levels of self-efficacy (p< 0.001) and grit (p=0.01). They also had fewer depressive symptoms (p=0.008), and less hopelessness (p = 0.01), stress at school (p=0.002) and stress about the future (p=0.03) reported in 11th grade. Conclusions School climate, and particularly an authoritative school environment, is strongly associated with better social-emotional health among adolescents. Relationship with teachers and their disciplinary style may be a focus for future interventions to improve the social-emotional health of children.